2014
DOI: 10.1155/2014/516183
|View full text |Cite
|
Sign up to set email alerts
|

Eye Diseases among Women Engaged in Local Extraction of Palm Kernel Oil in the Kumasi Metropolis

Abstract: The study aimed to determine the prevalence of eye diseases among women engaged in the local extraction of palm kernel oil in the Kumasi Metropolis. A cross-sectional study was carried out in five women groups purposively sampled. A total of 150 women were sampled. History taken from the women included participants' demographics and ocular and occupational history. Ocular examination included visual acuity and ophthalmoscopy. The Statistical Package for Social Sciences (SPSS) version 17.0 was used to analyze t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
1
5
1
Order By: Relevance
“…The overall prevalence of ocular morbidity (59.38%) reported in this study was lower than that reported in other high risk professions in Ghana [12,13] and elsewhere [14] but slightly higher compared to that reported by Kumah et al [15]. A plausible explanation for this could be the differences in sample size, age and sex of participants, and the difference in type of hazard and exposure time.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…The overall prevalence of ocular morbidity (59.38%) reported in this study was lower than that reported in other high risk professions in Ghana [12,13] and elsewhere [14] but slightly higher compared to that reported by Kumah et al [15]. A plausible explanation for this could be the differences in sample size, age and sex of participants, and the difference in type of hazard and exposure time.…”
Section: Discussioncontrasting
confidence: 80%
“…The high prevalence of conjunctival lesions is comparable to that found in other occupational based studies [12,13,[15][16][17]. Some literature [18,19] implicate the development of pterygium and pinguecula on hazardous environmental agents like heat, dust, oxides of chemicals, which are comparable to the harmful agents encountered by most of personnel of the fire service.…”
Section: Discussionsupporting
confidence: 74%
“…For example, artisanal miners in Ghana use elemental mercury in the extraction of gold but they typically do not wear any safety clothing while handling the mercury. [14][15][16][17][18] Generally, abattoirs across the country are characterized by poor sanitary conditions. It is a common observation that the surroundings of these abattoirs are always concentrated with heat and smoke from the burning of scrap lorry tyres used as fuel during treatment of animal hides.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 In addition, the crude processing techniques employed, the harsh working environments and the lack of use of protective equipment exposes these women to enormous amount of dust particles, smoke fumes, heat from the fires, oil splashes and injuries from flying nuts shells, which poses a great danger to their health. Kumah et al, 2014 also reported eye diseases among women engaged in local extraction of palm kernel oil in the Kumasi Metropolis of Ghana due to exposure to hydrogen sulphide, a component of smoke. 12,13 Prolonged periods of exposure to hazardous agents such as dust and biomass smoke on a regular basis predispose individuals to pulmonary problems such as asthma, obstructive and restrictive lung diseases and silicosis.…”
mentioning
confidence: 95%
“…Kumah et al, 2014 also reported eye diseases among women engaged in local extraction of palm kernel oil in the Kumasi Metropolis of Ghana due to exposure to hydrogen sulphide, a component of smoke. 12,13 Prolonged periods of exposure to hazardous agents such as dust and biomass smoke on a regular basis predispose individuals to pulmonary problems such as asthma, obstructive and restrictive lung diseases and silicosis. 14,15 Restrictive and obstructive lung diseases are often diagnosed through clinical examination and spirometry, the latter being a physiological test that measures how an individual inhales or exhales volumes of air as a function of time.…”
mentioning
confidence: 95%